(untitled) (Forum Penelitian Agro Ekonomi, 2017)
Agricultural material piracy as an illegal and imperialistic act may cause negative impacts such as: (a) violation on a country’s sovereignty, (b) negatively affects the economics of local communities, and (c) decrease or even destroy particular species or plant varieties. Such a piracy may be prevented by developing related laws and rules as well as enforcement policy. In a center-periphery relation, the primary problem of Indonesian scientific community lies on weak discursive power and lobbying capability. Furthermore, Indonesia’s position on socio-politics, economy and technology is also weak. Some alternatives to prevent biological piracy are developing related laws and rules, applying affirmative policy and social campaign on related action program.